EFFECT OF TRANSFORMATIONAL LEADERSHIP, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENTS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - AGUS PURWANTO; John Tampil Purba; Innocentius Bernarto; Rosdiana Sijabat (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The purpose of this study was to determine and examine the effect of transformational leadership, organizational commitment and job satisfaction on organizational citizenship behavior in high schools in Banten Province. The sample in this study was taken from 220 managers of supply chain management implemented company  respondents. Sampling in this study using the Simple Random Sampling technique. The analysis technique used is multiple regression analysis. The results of the analysis and testing show that transformational leadership has a positive and significant effect on  organizational citizenship behavior, job satisfaction has a positive and significant effect on organizational citizenship behavior, organizational commitment has a positive and significant effect on organizational citizenship behavior. This study has proven that transformational leadership, Organizational commitment and job satisfaction influence organizational citizenship behavior in supply chain management implemented company